Viabilidade da Silagem de Colostro para bezerros leiteiros - Gomide, Inês de Freitas (2017)
The use of milk substitute in calf feeding is a necessary practice to reduce production costs. The use of colostrum fermented anaerobically has become a reality for having low cost, but in the Triângulo Mineiro region, presented high loss rates. This thesis is divided into four chapters, the first one referring to the general considerations of the topics covered in the others. The second chapter aimed to analyze the colostrum silages of two rural properties in the city of Uberlândia in terms of quantification of total coliforms, Escherichia coli, Staphylococcus aureus, mesophilic bacteria and enterobacteria. After 30 days of fermentation the product was safe for use. However, 30.7% (23/75) of putrefaction losses were observed, which allowed the continuity of this study. In chapter III we aimed to evaluate the impact of the ambient temperature (TA) and the daily thermal amplitude (AT) on the loss index. In addition, to determine the impact of TA on the surface temperature of the package (TSE) and to verify if through TSE gauging can determine which samples will not present adequate fermentation. Colostrums were collected from six dairy cows from the Federal University of Uberlândia's batch and 108 samples of colostrum silage were prepared, which remained in the fermentation process for 7, 14 and 28 days. Of these samples, 46.4% (43/108) presented inadequacies due to putrefaction. It was concluded that the mean of TA and daily AT affect the fermentation and has a significant effect on the TSE, however, the TSE measurement is not a reliable method to determine the loss index. In the last chapter, the influence of pH, total coliforms, yeasts and molds, lactic bacteria and mesophilic bacteria on the suitability of the fermentation and its relation with the loss index of the samples were verified. It was concluded that the putrefaction process occurred starting from the seventh day of the fermentation process. Microbial contamination during this process was reduced by acidification of the pH, and the levels of these contaminations at 28 days can guarantee safety in the use of colostrum silage in feeding calves. However, the high index of losses due to putrefaction, probably due to contamination by yeasts and molds, demonstrates the need for strict sanitary control.